Laparoscopic left hemicolectomy for colo-colonic intussusception caused by sigmoid colon cancer - B A, Arifin; Sainal, Mohd. Yusof; Elagili, Faisal; Md Nor, Azmi (2022)
INTRODUCTION Adult intussusception is uncommon and is usually associated with carcinoma. Traditionally, an open technique with en bloc resection has been used to manage these. OBJECTIVE We present a case of colo-colonic intussusception caused by a sigmoid colonic tumour that was treated with am laparoscopic left colectomy and primary anastomosis. CASE REPORT An 80-year-old woman presented to the ER with bowel changes and abdominal pain that had been present for two weeks. She denied having lost weight and had no obstructive symptoms. She was discovered to be stable, apyretic, and cachectic. She was diagnosed with colo-colonic intussusception after a CT scan and colonoscopy, which was most likely caused by sigmoid colon cancer. During laparoscopic exploration, the intussusception was discovered. As a result, the bowel was removed via en bloc left hemicolectomy with primary anastomosis. Pathology of the resected specimen revealed a moderately differentiated adenocarcinoma (pT3N1aM0). The postoperative course of the patient was uneventful, and she was discharged on the sixth postoperative day. CONCLUSION Despite the fact that an open conventional method is the most commonly used, laparoscopic colectomy is expected to be an effective treatment strategy for adult colo-colonic intussusceptions caused by malignancy.